The Challenges of E-Learning Readiness Among UTHM Students Towards COVID-19 Situation - Ahmad, Nurul Syahirah Azli; Ahmad, Ahmad Nur Aizat; Ahmad, Md Fauzi b Ahmad (Research in Management of Technology and Business, 2024)
Since the case of COVID-19 rises, all institution faces new challenges whereby classes have to be conducted online. In the regards, students need to adapt with this new online learning environment by start setting their mind. This study investigates the challenges of electronic learning (e-learning) readiness among UTHM students during COVID-19 situation. Structured online questionnaire used in quantitative method were applied where involved a total of 375 respondents from UTHM undergraduate student at the main campus. Moreover, SPSS software has been used to analyse the data. The dimension of e-learning readiness focused on this research and listed as computer and internet self-efficacy, learner control, online communication self-efficacy, self-directed learning, and motivation for learning. The finding of this research showed that all the dimensions were recorded mean score at a high level and computer and internet self-efficacy was the highest mean score among the five dimensions. This research also found that lack of feedback was the most challenge faced by UTHM students. It concludes that the UTHM undergraduate student were ready to conduct the classes using e-learning.